Territorial policies for combating school dropout: reflections and considerations - Turano, Alessandro (Form@re - Open Journal per la formazione in rete, 2025)
Within the framework of European and international policies aimed at combating school dropout and enhancing the quality of education, the relationship between schools and local communities has once again become a focal point in the educational debate. The reflections presented in this contribution explore the tools and mechanisms for community participation in educational processes, highlighting their potential in fostering inclusive education and academic success. Policies territoriali per il contrasto alla dispersione scolastica. Note di riflessione. Nella cornice delle politiche europee e internazionali volte a contrastare la dispersione scolastica e a promuovere la qualità dell’istruzione, il tema della relazione tra scuola e territorio è tornato a impattare nel dibattito educativo. Le riflessioni contenute in questo contributo esplorano gli strumenti e i meccanismi di partecipazione della comunità nei processi educativi, e ne validano le potenzialità in un’ottica di inclusione formativa e successo scolastico.